Maternal Punitive Reactions to Children's Negative Emotions and Young Adult Trait Anger: Effect of Gender and Emotional Closeness - Perry, Nicole B. (Marriage Fam Rev, 2015)
The current study tested whether young adult’s recollected reports of their mother’s punitive reactions to their negative emotions in childhood predicted anger expression in young adulthood and whether emotional closeness weakens this association. Further, a three-way interaction was tested to examine whether emotional closeness is a stronger protective factor for young women than for young men. Results revealed a significant three-way interaction (gender X emotional closeness X maternal punitive reactions). For young men, maternal punitive reactions to negative emotions were directly associated with increased anger expressions. Maternal punitive reactions to young women’s negative emotions in childhood were associated with increased anger in adulthood only when they reported low maternal emotional closeness. Findings suggest that maternal emotional closeness may serve as a buffer against the negative effects of maternal punitive reactions for women’s anger expression in young adulthood.